Lower Admission Hemoglobin Levels Are Associated With Longer Symptom Duration in Acute ST‐Elevation Myocardial Infarction. Issue 2 (7th October 2013) - Shacham, Yacov; Leshem‐Rubinow, Eran; Ben‐Assa, Eyal; Roth, Arie; Steinvil, Arie
ABSTRACT Background An acute‐phase response in patients with acute myocardial infarction could contribute to the development of anemia. Hypothesis An association may exist between symptom duration, hemoglobin (Hb) concentration and serum C‐reactive protein (CRP) values in patients presenting to an emergency department (ED) with acute ST‐segment elevation myocardial infarction (STEMI). Methods A retrospective analysis was conducted on consecutive male STEMI patients who were admitted to our medical center's ED from January 2008 to November 2012 and had presented within the first 12 hours after the onset of chest pain. Hemoglobin concentration and serum CRP levels were determined from blood samples taken prior to any drug or fluid administration. Analyses of variance were used to determine interactions between selected time‐to‐presentation cutoffs and admission Hb and CRP concentrations. Patients with other reasons known to cause elevation of inflammatory markers, anemia, or bleeding diathesis were excluded. Results The study population comprised 718 patients whose mean age was 61 ± 12 years (range, 27–96 years). Blood was drawn for Hb and CRP measurements directly upon admission. Patients who presented to the ED within 3 hours of symptom onset had higher Hb concentrations (P = 0.048) and lower serum CRP levels (P < 0.001) compared with those who presented after a longer interval from symptom onset. Conclusions Longer symptom duration is associated with a lower admission Hb level and an early rise in the CRP level of male patients with acute STEMI.